Santayana’s Political Philosophy Updated in Poland: Review of: Katarzyna Kremplewska, George Santayana’s Political Hermeneutics. Value Inquiry Book Series, vol. 373, 2022, 261 páginas. - Moreno Moreno, Daniel (Analysis. Journal of Philosophical Research, 2023)
Review of: Katarzyna Kremplewska, George Santayana’s Political Hermeneutics. Value Inquiry Book Series, vol. 373, 2022, 261 páginas.